2020
DOI: 10.1136/gpsych-2020-100222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of hospitalised patients with schizophrenia who were suspected to have coronavirus disease (COVID-19) in Hubei Province, China

Abstract: BackgroundSince the outbreak of COVID-19, no data have been available for hospitalised psychiatric patients who are suspected to have COVID-19. We performed a comprehensive investigation of the clinical features of hospitalised patients with schizophrenia with or without suspected COVID-19 in Hubei Province, China.AimTo explore the clinical characteristics of hospitalised patients with schizophrenia with suspected COVID-19 in Hubei Province, China.Methods21 hospitalised patients with schizophrenia with suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
1
39
0
2
Order By: Relevance
“…Of these 237 articles were excluded, and the remaining 85 full text articles were reviewed. Fifteen studies were finally found to be eligible and table 2 provides the description of the included studies (Lara et al 2020; Berthelot et al 2020 ; Clerici et al 2020 ; Fernandez-Aranda et al 2020 ; Gonzalez-Sanguino et al 2020 ; Goodman-Casanova et al 2020 ; Hao et al 2020 ; Iancu et al 2005 ; Liu et al 2020 ; Maguire, Reay, and Looi 2019 ; Ozdin and Bayrak Ozdin 2020 ; Phillipou et al 2020 ; Van Der Heide and Coutinho 2006 ; Zhou et al 2020 ; Pang and Tam 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 237 articles were excluded, and the remaining 85 full text articles were reviewed. Fifteen studies were finally found to be eligible and table 2 provides the description of the included studies (Lara et al 2020; Berthelot et al 2020 ; Clerici et al 2020 ; Fernandez-Aranda et al 2020 ; Gonzalez-Sanguino et al 2020 ; Goodman-Casanova et al 2020 ; Hao et al 2020 ; Iancu et al 2005 ; Liu et al 2020 ; Maguire, Reay, and Looi 2019 ; Ozdin and Bayrak Ozdin 2020 ; Phillipou et al 2020 ; Van Der Heide and Coutinho 2006 ; Zhou et al 2020 ; Pang and Tam 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However a more recent study by Liu, et al (2020) which compared schizophrenic subjects who were suspected of having Covid 19 with those who were not suspected of the same, found no difference in PANSS scores in the two groups. They found that the Covid suspect group was found to have more anxiety, depression, stress and sleep problems than the comparator group ( Liu et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 1 available at provides a summary of characteristics of the included studies in this review. 2,4-50…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al 38 reported on 21 in-patients with schizophrenia who were transferred to an isolation unit of a psychiatric hospital for suspected COVID-19 infection. The comparison group included 30 in-patients with schizophrenia without any COVID-related symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Relapses of an already existing mental health condition are observed as well. 3 The isolation in departments caring for SARS-Cov-2 patients is multidimensional. Patients cannot leave the hospital, even if they are willing to bear the medical responsibility and consequences.…”
mentioning
confidence: 99%